Emerging Asia's growth and integration: how autonomous are business cycles? - Rasmus Rüffer; Marcelo Sánchez; Jian-Guang Shen (European Central Bank (ECB), 2007)
Against the background of the rapid integration of emerging Asia into the global economy, this paper investigates the role of domestic and external factors in driving individual emerging economies in Asia. We estimate VAR models for ten countries over the period 1979Q1- 2003Q4, controlling for external factors, and use sign restrictions to identify structural domestic shocks. Variance decompositions indicate that Asian emerging economies are to a large part driven by external developments, and even more so employing a more recent sample. We analyse to what extent structural domestic shocks exhibit a regional dimension by comparing shocks across countries using correlation and principal component analysis. The extent of regional co-movement between structural shocks is relatively limited. While the principal components analysis indicates a moderate increase in co-movement over time, the correlation analysis finds a decline. This may reflect a broadening of regional integration at the expense of bilateral economic ties.
Keywords: F15; F02; F41; 330; Economic integration; International Business Cycles; sign restrictions; structural shocks; Konjunkturzusammenhang; Strukturwandel; Schock; Regionale Wirtschaftsintegration; Schwellenländer; Asien